Can the spanish courts rule on the custody rights of a minor resident in Ecuador? Commentary on the judgment of the Provincial Court of Barcelona 468/2020 of 23 July 2020 - Durán Ayago, Antonia (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
A mother of ecuadorian nationality and resident in Spain applies to the Spanish courts for custody of her daughter who resides in Ecuador, cared for by her maternal grandmother. The court considers that it does not have competence to hear this procedure, for which Article 10 of the 1996 Hague Convention argues in an incomprehensible way in a procedure that is not matrimonial in nature,since the parents were not married. The appeal confirms the lack of international judicial competence on the basis of Article 5 of the Convention.
Keywords: parental responsibility; custody rights; international jurisdiction; habitual residence of the minor